Досвід визначення поняття «історичне джерело» з позицій філософської герменевтики - Лукашевич, О. А.; Lukashevich, A.; Лукашевич, А. А. (ЧНУ, 2016)
У статті розглядається проблема визначення поняття «історичне джерело» з позицій філософської герменевтики Г.-Г. Гадамера. Підставою такої спроби стали поява нових історичних джерел - електронних документів, а також актуальність некласичної наукової парадигми. При цьому була врахована суб’єкт-об’єктна природа походження та існування історичного джерела. The notional apparatus of historical science can serve cognitional purposes if it is renewed, modified each time when new empirical data, theoretical and methodological concepts appear. Due to this the phenomenon of digital heritage, non-classic scientific paradigm actualization, spreading of functional aims are considered as suppositions to re-comprehend the key notion of humanitarian knowledge – «historical source». The basis of the offered experience to formulate the notion is searching the ways to get over the logical contradiction: on the one hand, between polysubjective pole of historical cognition which is conditioned by the context in which historians are positioned and get their own results of research, and on the other hand, the research practice object – the primary source which in concrete cognitive situation is single, unchangeable conclusion and thus conditioning the only one true independent of experiencing subject.
The experience of defining the «historical source» notion from the position of philosophical hermeneutics
Опыт определения понятия "исторический источник" с позиций философской герменевтики
Keywords: історичне джерело; філософська герменевтика; електронний документ; суб’єкт-об’єктні відношення; інтерпретація; об’єктивність; historical source; the digital heritage; philosophical hermeneutics; objectivity; философская герменевтика; цифровое наследие; исторический источник; субъект-объектные отношения